Association of the Onset of Self-Feeding With Subsequent Suspected Developmental Coordination Disorder: A Prospective Cohort Study in China - Hua, Jing; Williams, Gareth J.; Barnett, Anna L.; Zhang, Jiajia; Jin, Hua; Xu, Manyun; Chen, Juan; Zhou, Yingchun; Gu, Guixiong; Du, Wenchong (Frontiers in Psychiatry, 2022)
Background: Successful self-feeding reflects the readiness of early motor development and environmental impacts, and the onset of self-feeding as a developmental milestone might be a predictor of subsequent motor development in children. In this study, we explored the association between the onset of self-feeding and childhood risk of Developmental Coordination Disorder in children from one-child and two-child families. Methods: We conducted a data-linkage prospective cohort study from 38 kindergartens in 6 cities in China. A total of 11,727 preschoolers were included in the final analysis and were assessed with the Movement Assessment Battery for Children-second edition (MABC-2) Test. The information on early self-feeding onset was obtained from parents. The mixed and multi-level logistic models utilizing a random intercept were used to investigate the associations between the onset time of self-feeding and subsequent motor performance. Results: The results showed that, compared with those beginning self-feeding at or younger than 12 months of age, children starting self-feeding at 13-24 months, 25-36 months, and later than 36 months, showed a decrease in their total MABC-2 scores of 2.181, 3.026 and 3.874, respectively; and had an increased risk of suspected DCD by 36.0%, 101.6%, 102.6% respectively; they also had 30.2%, 46.6%, 71.2% increased prevalence of at risk of suspected DCD, when adjusting for both child and family characteristics (each p<0.05). Significant associations were observed in fine motor, gross motor, and balance subtests (each p<0.05) in groups with a delayed onset of self-feeding. However, the strength of the associations was mitigated in the fine motor and balance subtests in children with a sibling. Conclusion: The delayed onset time of self-feeding acts as an early behavioural marker for later childhood motor impairment. Moreover, children with a sibling may benefit from additional interaction and their motor developmental pattern may be affected by the presence of a sibling.